(3GdcGaj aj GdMOjKs - (3Gdcdjfj, GdQGRj, GdSdSdj, GdHZOGOj, CHh LYaQ, eMeO Hf jYbhH Hf ESMGb, J (B329 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI(B: (3GdeYjTI(B. (3ONhd GdUhajI Ydi CHj YHO Gddg Ydjg GdSdGe hGMJLGLge Ydjg ajeG jfghf GdfGS Yfg ef WdH GdQRbs
(3BNQgG (B:s
(3Gddg YR hLd jbhd(B: (3dbO fUQce Gddg aj ehGWf cKjQI(B. (3aYOOfG Jdc GdehGWf acGfJ KeGfjf(B. (3gPG BNQ cJGH GdEjeGf hGdfPQ hGdcaGQGJ hjJdhg cJGH GdQhVI ef GdcGaj(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B145s
(3GdPQjYI HQbe(B: 96s
(3GdCYdGe(B: (3L(B7(3, U(B145s
(3GdPQjYI HQbe(B: 96s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis